Eemian and Vistulian (Weichselian) paleoenvironmental changes: A multi-proxy study of sediments and mammal remains from the Ławy paleolake (Eastern Poland). (20th February 2018) - Hrynowiecka, Anna; Żarski, Marcin; Jakubowski, Gwidon; Nadachowski, Adam; Pawłowska, Kamilla; Pawłowski, Dominik; Szymanek, Marcin; Nast, Dariusz
Abstract: The Eemian-Vistulian developmental history of the Ławy paleolake (Eastern Poland) has been studied by analysing records of micro- (pollen, Cladocera, Ostracoda), macrofossils (molluscs, mammal remains), the lithological record and radiocarbon dating from a 5.30 m sediment core. At Ławy, in the Paterebo stream valley, well-preserved mammal fossil remains accompanied by organic deposits have also been investigated. The results of the multi-proxy analyses suggest explicitly that the climate was the main driving force of the changes in terrestrial and aquatic ecosystems, and in the geomorphological processes in the catchment. However, we propose that the water level fluctuations were also an important factor in the modification of the aquatic assemblages. Pollen, cladocerans, molluscs and ostracods from Ławy indicate the existence of a small, shallow, well-vegetated paleolake during the warm Eemian climate optimum. In the final phase of the Eemian the lake was transformed into a mire. In the Early Vistulian, the variable hydrological conditions were the main driver force for the development of the study area. Finally the existence of the basin at Ławy was closely associated with periodic coexistence of limnic, telmatic and river environments.